Preparation and characterization of new polyimide films containing zeolite L and/or silica. (March 2014) - Hamciuc, Elena; Hamciuc, Corneliu; Musteata, Valentina Elena; Kalvachev, Yuri; Wolinska-Grabczyk, Aleksandra
New polyimide (PI) films containing zeolite L and/or silica, having a thickness of tens of micrometers, were prepared using a PI matrix with pendant carboxylic groups. The influence of various ratios of inorganic filler on thermal stability, dielectric behavior, and gas transport properties of the films was studied with respect to their structure. The surface morphology was investigated by scanning electron microscopy. The films were flexible, tough, and showed good thermal properties with a glass transition temperature in the range of 187–218°C. The dielectric spectroscopy revealed γ and β subglass transitions having the corresponding relaxation activation energy in the range of 44.7–51.4 kJ mol −1 and 65.1–121.6 kJ mol −1, respectively. At temperatures above 200°C, a conductivity relaxation process was evidenced. Gas permeation tests using small molecules (O2, N2 and CO2 ), at 6 atm and 30°C, indicated that the PI films containing higher amount of zeolite showed the highest permeability for all gases.